Evaluation of an upper-body strength test for the cross-country skiing sprint - Stöggl, T.; Lindinger, S.; Müller, E. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The scope of the study was (a) to develop a test concept for specific upper-body power and strength diagnostics of cross-country (XC) skiing sprint athletes, (b) to check test reliability and validity, and (c) to test the hypothesis that maximal power, explosive strength, and power-endurance predict double-poling (DP) sprint performance over race distance. Methods: Nineteen elite XC skiers performed test-retest of the two-phase test (2PT) on a rollerboard, with the four-repetition maximal test (4RmaxT) as phase 1 and the 40-repetition test (40RT) as phase 2, both for determination of specific upper-body power and explosive strength. To check validity, 31 subjects performed the 2PT and a DP sprint test for 50 m, and a subgroup (N = 19) also performed a DP maximal-speed test and a 1000-m DP sprint test, both on a treadmill. Results: The 4RmaxT was highly reliable (r = 0.90-0.99, P < 0.001), except for explosive force and time to peak force. The 40RT was highly reliable for all variables concerning velocity and power (r = 0.92-0.99, P < 0.001). Peak lactate showed only low reliability (r = 0.69, P < 0.01). The peak values (maximal power, peak velocity, etc.) measured in the 4RmaxT contributed to up to 84% of the variation in 50-m DP sprint time and up to 61% of the variation in 1000-m performance. Moderate to high correlations in 1000-m DP sprint performance were found between the mean values and the fatigue indices of the 40RT. Conclusions: The 2PT is a reliable, valid, short-lasting test. The relationship between maximal power output (measured in the 4RmaxT) to 50- and 1000-m sprint performance suggests increasing the proportion of training aimed at the improvement of specific explosive strength and maximal power.